Artikel Efektifitas Google Form Sebagai Media Evaluasi Di Masa Pandemi - Ni Nyoman Sri Aryanti (Cetta: Jurnal Ilmu Pendidikan, 2021)
This study aims to determine the effectiveness of google form as a medium for evaluating theme learning in sixth grade in the midst of the Covid-19 pandemic. The evaluation process in elementary schools is generally carried out through meetings of educators and students in the classroom and in the school area. However, during the Covid-19 epidemic like today, which requires everyone to keep their distance and avoid physical contact, the evaluation process that has been taking place at school cannot be carried out and is replaced by an online learning model. This condition becomes an obstacle in the teaching and learning process, especially for educators to find the easiest alternative solution so that they can still evaluate learning on students. This article was created using the literature study method, which describes in detail the effectiveness of using Google Form as an evaluation medium compiled from scientific articles, the internet and other sources relevant to the topic being the object of research. The criteria for the articles and news that are chosen are about the effectiveness of using Google Form as an evaluation medium. From various sources obtained, then the most relevant was selected and 5 articles were obtained which showed that Google Form was effectively used as an evaluation medium.